WELL PERFORMANCE ANALYSIS BASED ON FLOW CALCULATIONS AND IPR (Journal of Engineering, 2006)
A study has been done to analyze the total production system by developing a computer model. Everycomponent of the production system has been programmed individually and then linked in the compositeproduction system computer program. These components are; reservoir component, vertical component,surface choke component and finally horizontal component.Each of the previous components are developed using various equations or models to determine thepressure loss thorough that component. In the current study the Wiggins method has been used tocalculate the IPR curves. The vertical and horizontal components are developed using the unifiedmechanistic model of Gomez. Lage mechanistic model has been used to calculate the pressure lossesthrough annulus. Perkins mechanistic model is used to calculate the pressure loss through surface chokes.A filed example problem is presented to analyze the production system. This example has been usedto determine the optimum system design which maximizes production rate for a set of condition.